Frequency of Intestinal Parasites in Patients with Diabetes - Şahin, Maksut; Taş-Cengiz, Zeynep; Halidi, Ahmed Galip; Aydemi̇r, Selahattin; Ekici, Abdurrahman (Yuzuncu Yil Universitesi Tip Fakultesi, 2025)
This study aims to determine whether patients with diabetes are at risk for intestinal parasites. The study included 200 diabetics and 150 healthy i ndividuals without any chronic disease. Data such as age, gender, diagnosis, and patient laboratory test results were obtained from the hospital automation system. Stool samples were examined by native-Lugol, concentration, modified acid-fast, and trichrome staining methods. Intestinal parasites were found in 27.5% of the diabetic patients and 14% in the control group; the difference between the two groups was statistically significant (p=0.001). Out of 200 patients, Blastocystis hominis was found in 44 (22%), Cryptosporidium spp. in one (0.5%), B. hominis and Entamoeba coli in five (2.5%), Giardia intestinalis in two (1%), B. hominis and G. intestinalis in one (0.5%), Taenia spp. in one (0.5%) and Chilomastix mesnili in one (0.5%). In the diabetic patient group, statistically significant differences were found between age (p=0.043), duration of diabetes (p=0.006), fasting blood glucose (p=0.028) and HbA1c value (p=0.01) and presence of intestinal parasites. No statistically significant differences were found between place of residence, biochemical values such as cholesterol and LDL, use of insulin and antidiabetic agents, presence of another disease such as hypertension, COPD, neuropathy, nephropathy and intestinal parasite positivity. Patients with diabetes can be considered a risk group in terms of intestinal parasite infections. Furthermore, individuals with a history of diabetes of more than 10 years and poor glycemic control are at a higher risk for intestinal parasites. © 2025 Elsevier B.V., All rights reserved.
Keywords: Diabetes; Hba1c; Intestinal Parasites; Native-lugol; Cholesterol; Hemoglobin A1c; Insulin; Lugol; Antidiabetic Agent; Cholesterol; Hemoglobin A1c; Insulin; Low Density Lipoprotein; Lugol; Age; Aged; Article; Biochemistry; Blastocystis Hominis; Child; Chilomastix; Chronic Disease; Chronic Obstructive Lung Disease; Controlled Study; Cryptosporidium; Cyclospora; Cyclospora Cayetanensis; Cystoisospora Belli; Diabetes Mellitus; Diabetic Patient; Disease Duration; Entamoeba Coli; Enterobius Vermicularis; Feces Analysis; Female; Frequency; Gender; Giardia Intestinalis; Glucose Blood Level; Human; Hypertension; Intestine Parasite; Kidney Disease; Major Clinical Study; Male; Masson Staining; Neuropathy; Preschool Child; Residence Characteristics; Taenia; Trophozoite; Very Elderly